Cat and cocky - Gray, Nigel; Pearson, David (Macmillan Education Australia South Yarra, Vic., 1998)
Cat and Cocky by Nigel Gray is a delightful children's book that tells the story of an unlikely friendship between a clever cat and a spirited cockatoo. As the two characters navigate their differences and embark on various adventures, they discover the importance of cooperation, loyalty, and understanding. The playful interactions between Cat and Cock